Representasi Kesetaraan Gender dalam Partisipasi Politik pada Seral Drama Korea "Queen Maker" (Analisis Semiotika Roland Barthes) - Ira Rahau; Anjang Priliantini (Jurnal Komunikasi Massa, 2025)
Nowadays, the position of women in political participation still shows disparity, where the minimum legislative seat quota of 30% has not been met. Although the government has made several efforts through laws that guarantee women's equal rights in politics, the set minimum quota has yet to be achieved. The traditional roles and gender division between men and women serve as obstacles for women to participate in the public sphere, making it necessary to raise public awareness of this phenomenon. In the modern era, increasing public awareness of social phenomena can be illustrated through visual media such as films or drama series. One example is the Korean drama series "Queen Maker", which highlights the theme of gender equality, particularly women's participation in politics. This research aims to identify the signs of gender equality in political participation in the Korean drama series "Queen Maker". This qualitative research uses a theory of representation and Roland Barthes' semiotic analysis, which focuses on signs. The results show that the Korean drama series "Queen Maker" contains representations of equality based on the indicators of gender equality according to BAPPENAS, namely access, participation, control, and benefits.